Taxonomy of the rivorum species-group of Leucania Ochsenheimer, 1816 (Lepidoptera: Noctuidae) - Dolibaina, Diego Rodrigo; Casagrande, Mirna Martins; Specht, Alexandre; Mielke, Olaf Hermann Hendrik; Legrain, Albert; Zilli, Alberto; Goldstein, Paul (Zootaxa, 2019)
The rivorum species-group of the genus Leucania (Noctuidae: Noctuinae: Leucaniini) is circumscribed and taxonomically revised, with the inclusion of three species. New taxonomic hypotheses were achieved through the morphological analysis of about 250 specimens allied to the type material of L. rivorum Guenée, 1852; L. pampa Schaus, 1894, stat. rev.; and Neleucania multistria Köhler, 1947, stat. rev., the last two resurrected from synonymy with L. rivorum and Dargida lithophilus (Butler, 1882), respectively. Adult habitus and morphology of the genitalia support the transfer of Neleucania multistria to Leucania, comb. nov. Lectotypes for L. rivorum and L. pampa are designated to ensure nomenclatural stability and recognizability of these taxa. Additionally, the similar, rust-colored species Leucania chejela (Schaus, 1921) is compared with species of the rivorum species-group, and is recorded from South America for the first time. All species of the rivorum group are re-described, with high-resolution images of taxonomic characters of the adults (head, patagium, and male and female genitalia), and updated distributional maps presented.